2006
DOI: 10.1111/j.1468-1293.2006.00346.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, 96‐week study of the impact of Trizivir®, Combivir®/nelfinavir, and lamivudine/stavudine/nelfinavir on lipids, metabolic parameters and efficacy in antiretroviral‐naive patients: effect of sex and ethnicity

Abstract: To compare the lipid and metabolic effects, efficacy, and safety of twice-daily regimens of Trizivir s (abacavir 300 mg/lamivudine 150 mg/zidovudine 300 mg triple nucleoside tablet; TZV), Combivir s (lamivudine 150 mg/zidovudine 300 mg combination tablet; COM) 1 nelfinavir (NFV), and stavudine (d4 T) 1 lamivudine (3TC) 1 NFV. Study designAn international, phase 4, open-label, parallel-group, 34-centre study was conducted in 254 nondiabetic, antiretroviral-naive, HIV-infected out-patients with an HIV-1 RNA leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 25 publications
1
42
0
Order By: Relevance
“…The extent to which these metabolic side effects, like dyslipidemia, vary in different ethnic or ancestral populations has been demonstrated by a number of studies, but the racial effects seen are not necessarily consistent across studies. [25][26][27] In general, these studies found that whites had more atherogenic lipid profiles in response to HAART than blacks or hispanics. Overall our results agree with these findings, but the HAART-associated change in specific lipid phenotypes does vary from previous reports.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The extent to which these metabolic side effects, like dyslipidemia, vary in different ethnic or ancestral populations has been demonstrated by a number of studies, but the racial effects seen are not necessarily consistent across studies. [25][26][27] In general, these studies found that whites had more atherogenic lipid profiles in response to HAART than blacks or hispanics. Overall our results agree with these findings, but the HAART-associated change in specific lipid phenotypes does vary from previous reports.…”
Section: Discussionmentioning
confidence: 91%
“…[16][17][18][19][20][21][22][23][24] Previous studies associating dyslipidemia with specific drug combinations used in HAART have also shown that the extent of dyslipidemia tends to vary between self-reported racial populations. [25][26][27][28] Serum lipid levels, atherosclerosis, and CVD risk are all known to vary by race in the general population and polymorphisms in genes involved in cholesterol transport and metabolism may play a role in this variation. [29][30][31][32][33][34][35][36] Investigating lipid patterns by self-reported race may be complicated by the heterogeneous genetic profiles of individuals in those self-classified populations.…”
mentioning
confidence: 99%
“…The Context Study, which assessed treatment-experienced patients, reported a discontinuation rate of 47% in women compared with 22% in men; however, women comprised only 15% of the 315 patients enrolled, limiting the interpretation of these data. 9 Additionally, in a study that enrolled 254 patients, including a high proportion of women (50%), black (40%), and Hispanic (37%) treatment-naïve patients, Kumar et al 18 reported an overall discontinuation rate of 49%; specific differences by sex were not reported. The Women First Study was specifically designed to assess the efficacy and safety of combination ARV therapy in protease inhibitor-naïve women and also to evaluate treatment compliance and continued study participation.…”
Section: Discussionmentioning
confidence: 99%
“…Fasting triglyceride elevations were more common in men than women, as has been observed in other ARV trials that enrolled either treatment-naïve or treatment-experienced patients. [4][5][6][7] The incidence of LDL elevations was numerically higher in women than men; this is supported by the cross-sectional FRAM (Fat Redistribution And Metabolic change) study, which recently demonstrated that HIV-infected women had higher LDL levels compared to uninfected women. In contrast, HIV-infected men had lower LDL levels than uninfected men, 13,14 suggesting the LDL elevations may be more prevalent in HIV-infected women than men.…”
Section: Discussionmentioning
confidence: 91%
“…[4][5][6][7] For instance, men receiving ARV therapy are more commonly reported to develop hypertriglyceridemia compared to women. [5][6][7] Few of these trials, however, have enrolled a population of women large enough to draw definitive genderbased conclusions regarding metabolic effects of individual ARV agents.…”
Section: Introductionmentioning
confidence: 99%